Implementation of the Electronic Performance System for State Civil Apparatus at the Tenggarong Seberang Sub-District Office - Okinu Rahim; Adam Idris; Santi Rande (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study explores the implementation of the Electronic Performance System for State Civil Apparatus at the Tenggarong Seberang Sub-District Office, Kutai Kartanegara Regency. The system was developed as part of the Indonesian government's broader strategy to improve bureaucratic performance and accountability through the application of digital governance (e-government). The research applies to a qualitative descriptive method with data collected through field observations, in-depth interviews, document analysis, and literature review. Key aspects examined include communication, resource availability, disposition or willingness of implementers, and bureaucratic structure drawing from the policy implementation model of George C. Edwards III. The findings reveal that while the transmission and clarity of the E-Kinerja policy are adequately established through training and socialization activities, the consistency of its application varies among staff. A significant challenge lies in the limited understanding and technical capacity of certain employees to operate the system effectively. In addition, the absence of specific financial resources to support the digital infrastructure and recurring system errors further hinder smooth implementation. However, a strong disposition among the staff and legal support from national regulations such as BKN Regulation No. 7/2023 act as positive factors reinforcing the system’s use. This research concludes that the successful implementation of E-Kinerja depends not only on the system's technical robustness but also on human resource readiness, leadership commitment, and the integration of organizational routines. The case of the Tenggarong Seberang Sub-District Office illustrates both the opportunities and constraints that local governments face in translating central government digital policy into effective administrative practice. The study offers insights for future improvements in performance-based management systems within Indonesia’s public sector.